Enzymatic assisted citronella essential oil extraction from cymbopogan winterianus - Norhidayah Abd Aziz author (School of Bioprocess Engineering, University Malaysia Perlis, 2015)
The study was conducted to improve the yield of citronella oil recovery by introducing an optimised enzymatic assisted pre-treatment using crude microbial enzymes isolated from the soil surrounding the citronella roots. Firstly, the lignocellulosic components of dried citronella roots were investigated to evaluate the most abundance component for selection of enzymes useful for pre-treatment. The composition analysis has identified cellulose as the major lignocellulosic component (38.21%1.65), followed by hemicellulose (30.49%0.93), lignin (21.12%1.86) and extractives (4.97%0.22). 31 out of 52 isolated strains have been identified as positive cellulase producer.